Coefficient of friction equation for gears based on a modified Hersey parameter - Carlos M C G Fernandes (2016)
The present work is first of all a bibliographic revision about the coefficient of friction equations forgears. The available expressions were compared and used to predict experimental results trying to draw an overview about the main advantages and disadvantages of each method. A load sharing function to predict the coefficient of friction was developed based on a modified Hersey parameter. A coefficient of friction equation is then proposed trying to improve the existing methods, including the influence of the oil pressure-viscosity parameter, on the coefficient of friction. The new equation correlates very well with the experimental results.